Digital processing of images of nano-dimensional elements on nanostructured material surface using the ImageJ software - H. T. Dinh; N. V. Lushpa; K. V. Chernyakova; I. A. Vrublevsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The paper presents methods for improving the quality of SEM images of the surface of nanoporous anodic aluminum oxide. The algorithm of the pore size determination using ImageJ software was described. The proposed algorithm is based on the analysis of large data arrays taken from the limited surface areas. The distribution of pore diameter depending on their quantity is presented. The parameters of surface morphology of nanoporous anodic alumina films obtained in the present study agree with literature data.